2015
DOI: 10.1099/jmm.0.082263-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenemase and cephalosporinase genes among clinical isolates of Acinetobacter baumannii in a tertiary medical centre in Malaysia

Abstract: Antimicrobial resistance in Acinetobacter baumannii is a growing public health concern and an important pathogen in nosocomial infections. We investigated the genes involved in resistance to carbapenems and cephalosporins in clinical A. baumannii isolates from a tertiary medical centre in Malaysia. A. baumannii was isolated from 167 clinical specimens and identified by sequencing of the 16S rRNA and rpoB genes. The MIC for imipenem, meropenem, ceftazidime and cefepime were determined by the E-test method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Likewise, A. baumannii isolates collected in 2010 and 2011 from various ward in HSA in the southern state of Johor, displayed resistance rates of 88% for both imipenem and meropenem ( Dhanoa et al, 2015 ). Resistance rates of >70% were also reported for isolates from UKMMC (located south of Kuala Lumpur) in 2010–2011 ( Biglari et al, 2015 , 2017 ) and HSNZ (located in the east coast state of Terengganu) in 2011( Lean et al, 2014 ).…”
Section: Antibiotic Susceptibility Profilesmentioning
confidence: 77%
See 1 more Smart Citation
“…Likewise, A. baumannii isolates collected in 2010 and 2011 from various ward in HSA in the southern state of Johor, displayed resistance rates of 88% for both imipenem and meropenem ( Dhanoa et al, 2015 ). Resistance rates of >70% were also reported for isolates from UKMMC (located south of Kuala Lumpur) in 2010–2011 ( Biglari et al, 2015 , 2017 ) and HSNZ (located in the east coast state of Terengganu) in 2011( Lean et al, 2014 ).…”
Section: Antibiotic Susceptibility Profilesmentioning
confidence: 77%
“…Data from the National Surveillance for Antibiotic Resistance (NSAR) is included and labeled as “NSAR” in purple-colored fonts. Data from the other studies are as follows: UMMC from 1987 and between 1996 and 1998, ( Misbah et al, 2004 ); HUSM between 2003 and 2006, ( Deris et al, 2009 ); and between 2005 and 2009, ( Ariffin et al, 2012 ); UMMC between 2008 and 2009, ( Dhabaan et al, 2012 ); Hospital Selayang (H. SLYG) in 2010, ( Nazmul et al, 2012 ); UKMMC between 2010 and 2011, ( Biglari et al, 2015 , 2017 ); Various, collected from various hospitals mainly around the town of Ipoh in the state of Perak in 2010 and 2011, ( Kor et al, 2014 ); HSNZ in 2011, ( Lean et al, 2014 ); and Hospital Sultanah Aminah (HSA) between 2011 and 2012 ( Dhanoa et al, 2015 ).…”
Section: Antibiotic Susceptibility Profilesmentioning
confidence: 99%
“…Except for mcr-4.3, this strain harbors the naturally occurring bla OXA-51-like (bla OXA-430 with additional H7Q and S90G mutations) and bla ADC-like (bla ADC-184 with an additional P113S mutation) genes in A. baumannii (16). The ISAba1 element can provide a promoter to upregulate the expression of bla ADC or bla OXA , leading to resistance to cephalosporins or carbapenems in A. baumannii (17,18). No ISAba1 element was found upstream of the bla OXA-51-like and bla ADC-like genes in AB18PR065.…”
Section: Resultsmentioning
confidence: 99%
“…This was similar to the result in 2010, where data from 16 microbiology laboratories showed that 56.8% of 9,481 isolates were resistant to meropenem (121). The OXA-23 gene was the major carbapenemase gene associated with carbapenem resistance in AB at a single Malaysian institute (122), and a regional study involving a small collection of CRAB isolates from Malaysia found that these belonged to global clone II (8).…”
Section: Southeast Asiamentioning
confidence: 99%